2017
DOI: 10.1021/acs.jmedchem.6b01473
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Guided Design of EED Binders Allosterically Inhibiting the Epigenetic Polycomb Repressive Complex 2 (PRC2) Methyltransferase

Abstract: PRC2 is a multisubunit methyltransferase involved in epigenetic regulation of early embryonic development and cell growth. The catalytic subunit EZH2 methylates primarily lysine 27 of histone H3, leading to chromatin compaction and repression of tumor suppressor genes. Inhibiting this activity by small molecules targeting EZH2 was shown to result in antitumor efficacy. Here, we describe the optimization of a chemical series representing a new class of PRC2 inhibitors which acts allosterically via the trimethyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 33 publications
(78 reference statements)
2
49
0
Order By: Relevance
“…In an effort to improve selectivity of ritanserin for DGKα, we explored ligand deconstruction (Hajduk et al, 2000; Kozakov et al, 2015; Lingel et al, 2017) strategies to evaluate the contributions of representative fragments for binding affinity and selectivity. We hypothesized that the 4-substituted piperidine moiety of ritanserin (highlighted in red, Figure 7C) is a likely pharmacophore required for DGKα inhibition because of conservation of this motif across several DGKα inhibitors (Boroda et al, 2017) (Figure S3E).…”
Section: Resultsmentioning
confidence: 99%
“…In an effort to improve selectivity of ritanserin for DGKα, we explored ligand deconstruction (Hajduk et al, 2000; Kozakov et al, 2015; Lingel et al, 2017) strategies to evaluate the contributions of representative fragments for binding affinity and selectivity. We hypothesized that the 4-substituted piperidine moiety of ritanserin (highlighted in red, Figure 7C) is a likely pharmacophore required for DGKα inhibition because of conservation of this motif across several DGKα inhibitors (Boroda et al, 2017) (Figure S3E).…”
Section: Resultsmentioning
confidence: 99%
“…During early development of porcine embryos, DNA methylation decreases to a minimum after ZGA at the 8-cell stage, and is re-established in blastocysts. [31][32][33] We observed that EZH2 showed significant high expression in the 8-cell embryo and SUZ12 was remarkably high in the morula and EB ( Figure 6C). H3K4me3 is related to activation of gene transcription, 30,31 and the regulators SETD1A and SETD1B were remarkably high in the 8-cell embryo when ZGA occured, and then the expressions decreased in EB ( Figure 6B).…”
Section: Expression Dynamics Of Epigenetic Regulators During the Emmentioning
confidence: 86%
“…Collectively, this information has been very helpful for guiding the lead optimization effort. The manuscripts for the optimization results for EED210 and EED162 will be published separately [24, 39, 40]. In conclusion, we have discovered a new class of PRC2 allosteric inhibitors through binding to EED.…”
Section: Discussionmentioning
confidence: 99%